Spatial and Temporal Distribution Characteristics and Value Cognition of Shaanxi’s Hospital Heritage - Jing Lv; Haozhong Yang; Yalan Chen; Kecheng Du; Shuai Wang; Mengchen Li; Tingting Zhao (Buildings)
This study investigates 101 hospital heritage sites in Shaanxi (1889–1992). It addresses the lack of a standardized definition and fragmented research on Chinese hospital heritage. Data were collected from Shaanxi local records, hospital architectural documents, and satellite imagery. These were supplemented by interviews with 33 stakeholders directly involved in or associated with hospital heritage conservation to assess heritage values. GIS analysis revealed four distinct spatiotemporal stages: Introduction of Western medicine (1889–1936), Medical care in time of war (1937–1949), The healthcare system after the establishment of PRC (1950–1978), and Healthcare reform in the context of economic transition (1979–1992). Significant regional disparities were observed across these stages. Spatiotemporal analysis of historical and contemporary satellite imagery revealed three conservation patterns of original sites. To assess multidimensional values, grounded theory analysis identified nine main dimensions (including emotional significance, cluster value, and technological heritage) with 31 initial categories exhibiting complex interdependencies. Collectively, the findings highlight systemic challenges in Shaanxi’s hospital heritage conservation, particularly neglect and incompatible reuse, underscoring urgent protection needs. This framework provides theoretical underpinnings for optimizing hospital heritage resource allocation and implementing sustainable conservation strategies.